Lifespan issues: studies on psychological well-being from educational perspective - Abd. Hamid, Siti Rafiah (Institut Terjemahan & Buku Malaysia Berhad, 2016)
This book is a collection of empirical studies in Educational Psychology and Counseling. It generally focuses on three major themes namely: Aspects od psychological well-being, happiness and life satisfaction. Studies on adolescents' and adults' psychological well-being, happiness and life satisfaction were examined. This book shares findings from studies which are qualitative and quantitative by nature. The readers will find the chapters which discuss findings realted to the psychological well-being and life satisfaction across the lifespan. It starts with the exploration of the deeper meaning of psychological well-being, happiness and life satisfaction, as well as the realitonship between them. The importance of Islamic perspectives on these issues was also discussed. The biggest portion discusses adolescents' developmental issues namely: Self, personality, social, moral and spiritual competency, IQ and school achievement, coping with peer pressure, dying and death.